Pengaruh Perencanaan Pajak, Penjualan Bersih, Manajemen Laba dan Profitabilitas terhadap Pajak Penghasilan Badan Terutang - Siti Mariah; Harry Barli (AKUNTANSI 45, 2025)
This study aims to determine the influence of Tax Planning, Net Sales, Earnings Management, and Profitability on Corporate Income Tax Payable in Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The measurement of corporate income tax payable is measured by the value of corporate income tax in the annual report. The sampling method used in this study is a purposive sampling method using Eviews 12 for data analysis. The data source in this study is quantitative data derived from annual financial reports with companies used as research samples with an observation period of 5 (five) years, resulting in a total sample of 65 samples. The analysis technique used is panel data regression. The results of this study indicate that the variables of tax planning, net sales, and profitability affect corporate income tax payable. Meanwhile, the variable of earnings management does not affect corporate income tax payable.